Evaluation of Mollugo oppositifolia Linn. as cholinesterase and β-secretase enzymes inhibitor - Das, Bhaskar; Bhardwaj, Pardeep K.; Sharma, Nanaocha; Sarkar, Arnab; Haldar, Pallab Kanti; Mukherjee, Pulok K. (Frontiers in Pharmacology, 2023)
Mollugo oppositifolia Linn. is traditionally used in neurological complications. The study aimed to investigate in-vitro neuroprotective effect of the plant extracts through testing against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and β-secretase linked to Alzheimer’s disease (AD). To understand the safety aspects, the extracts were tested for CYP450 isozymes and human hepatocellular carcinoma cell (HepG2) inhibitory potential. The heavy metal contents were estimated using atomic absorption spectroscopy (AAS). Further, the antioxidant capacities as well as total phenolic content (TPC), and total flavonoid content (TFC) were measured spectrophotometrically. UPLC-QTOF-MS/MS analysis was employed to identify phytometabolites present in the extract. The interactions of the ligands with the target proteins (AChE, BChE, and BACE-1) were studied using AutoDockTools 1.5.6. The results showed that M. oppositifolia extract has more selectivity towards BChE (IC50 = 278.23±1.89 μg/mL) as compared to AChE (IC50 = 322.87±2.05 μg/mL). The IC50 value against β-secretase was 173.93 µg/mL. The extract showed a CC50 value of 965.45 ± 3.07 µg/mL against HepG2 cells and the AAS analysis showed traces of lead 0.02±0.001 which was found to be within the WHO prescribed limits. Moreover, the IC50 values against CYP3A4 (477.03±2.01 µg/mL) and CYP2D6 (249.65±2.46 µg/mL) isozymes justify the safety aspects of the extract. The in silico molecular docking analysis of the target enzymes showed that the compound menthoside was found to be the most stable and showed a good docking score among all the identified metabolites. Keeping in mind the multi-targeted drug approach, the present findings suggested that M. oppositifolia extract have anti-Alzheimer’s potential.